THE CORRELATION BETWEEN STUDENTS’ FAMILY SUPPORT AND ENGLISH LEARNING ACHIEVEMENT OF THE THIRD-YEAR STUDENTS AT THE ENGLISH STUDY PROGRAM OF UNIVERSITAS RIAU - Aldo Irsyaf Putra; Novitri Novitri; Erni Erni; Zaldi Harfal (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2022)
This correlation research was conducted to discover the correlation between students’ family support and English learning achievement of third-yearstudents at the English study program of Universitas Riau. The instruments of the research were the students’ family support questionnaire and thestudent’s English learning achievement scores. The questionnaire, which consisted of 34 questions, was adapted from the Social Family SupportScale and adapted from Thoriq in 2013. The students’ English learning achievement was gained from their GPA (Grade Point Average) of Englishlanguage skills subjects; Listening Comprehension 1, 2, 3; Speaking 1, 2, 3; Reading Comprehension 1, 2, 3; and Writing 1, 2, 3. The population ofthis research was the third-semester students of the English study program at Universitas Riau, which comprised 110 students. A cluster randomsampling technique was used and this research involved 89 students as samples. The results show that the correlation between students’ familysupport and their English language skill learning achievement was categorized in the “moderate level”, the family support level was categorized as“high level” and their English language skills learning achievement was classified as “good level” and it was categorized as B+, and thecontribution of students’ family support for their English language skills learning achievement is 16.9%.